Peat soil treatment using transformed egg shells (tes) as chemical stabilizer - Jessie, Tiong Kung Yen (2016)
Organic soil is abundant in Malaysia due to tropical climate and topographical conditions. Generally, organic soil is low in shear strength due to high moisture retention property. Among all the practices, in-situ soil stabilization is found to be effective in treating soil. Researchers strive in finding sustainable and effective substitute to the conventional stabilizers: quicklime. Transformed egg shells were thought to be a potential substitute to quicklime. Calcium rich egg shells can be treated under complete disinfection and combustion to produce Calcium Oxide (CaO) component. Meanwhile, Calcium Carbonate is component that can be obtained by disinfection and grinding of egg shells. Transformed egg shells possess similar physical and chemical properties as in quicklime. In this study, transformed egg shells were tested in stabilizing organic soil from Pekan, Pahang. Unconfined shear strength (UCS) was conducted by investigating peak shear strength of soil stabilized after curing for 7, 14 and 28 days respectively. Results show that transformed egg shells have significant potential to stabilize organic soil for construction purpose